Biorregulador no desempenho agronômico, econômico e na qualidade de semente de soja - Albrecht, Leandro Paiola (2009)
The objective of this study was to evaluate the plants agronomic characteristics, yield components, seed physiological and health quality, and seed chemical composition, and also the economic viability in response to the Stimulate® bioregulator application in soybean crop. Thus, seeds of soybean cultivar BRS 46 RR was sown in October of the agricultural years of 2007/2008 and 2008/2009, using the experimental design in randomized blocks with four replications. The treatments, arranged in factorial design, were composed by combining the bioregulator seed treatment (without and with 0.500 L 100 kg-1 seed) and five doses of the product (0, 0.125, 0.250, 0.375 and 0.500 L ha-1) in foliar pulverization in two stages of development of soybean crop (V5 or R3). The product consists of three plant growth regulators in the following concentrations: 0.005% of IBA, 0.009% of kinetin and 0.005% of gibberellic acid. The use of growth regulator Stimulate® in soybean agronomic traits influences and increases productivity, the used growth regulator influences the seeds quality, especially when the applications were done at V5; the concentrations of oil and protein are altered by the action of growth regulator with a tendency to favor the protein content rather than oil; from the economic point of view, single leaf profitable were equal or exceed the record dose; the seed treatment may be an option of a safety economic return and, when choosing between the foliar V5 and R3, the recommended is the V5.